Gestión de recursos humanos y desempeño laboral área de personal en la Universidad Nacional de la Amazonia Peruana Iquitos 2025 - Grandez Arimuya, Flor de Maria (2025)
This study aimed to understand how human resource management impacts the daily performance of the work team at the National University of the Peruvian Amazon in Iquitos during the year 2025. To achieve this, a quantitative approach was used that allowed observing and analyzing the relationship between these two aspects without directly intervening in them. Questionnaires and reliable tools were applied to ensure the quality of the information collected; in fact, the results showed high internal consistency, with indices reflecting that the questions were clear and well-structured. The most interesting finding was discovering, through statistical analysis, that there is a very strong and positive connection between how human resources are managed and the work team's job performance, with a confidence level supporting these findings. In summary, this study confirms that when human resource management is properly conducted, it has a real and significant effect on people's performance, which is fundamental for the success of any organization. The hypothesis that motivated this research concludes that strengthening practices related to recruitment, leadership, and organizational climate improves worker performance, recommending the implementation of strategies that optimize these processes for institutional development.